2003
DOI: 10.1016/s0889-5406(02)56911-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various surface-conditioning methods on the bond strength of metal brackets to ceramic surfaces

Abstract: With the increase in adult orthodontic treatment comes the need to find a reliable method for bonding orthodontic brackets onto metal or ceramic crowns and fixed partial dentures. In this study, shear bond strength and surface roughness tests were used to examine the effect of 4 different surface conditioning methods: fine diamond bur, sandblasting, 5% hydrofluoric acid, and silica coating for bonding metal brackets to ceramic surfaces of feldspathic porcelain. Sandblasting and hydrofluoric acid were further t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(110 citation statements)
references
References 35 publications
6
96
1
7
Order By: Relevance
“…With regard to the bond strength required for adequate bonding of the orthodontic metal bracket, Maijer et al [52] suggested that the minimum bond strength required for dental clinical use is 5.9–7.9 MPa and Schmage et al [40] proposed that 6–10 MPa strength is necessary to support normal orthodontic forces. Based on these studies, groups treated with MDP (AM group, 11.92 ± 1.51 MPa) and MDP containing silane primers (AMS group, 13.36 ± 2.31 MPa) after sandblasting were shown to have sufficient bond strength (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the bond strength required for adequate bonding of the orthodontic metal bracket, Maijer et al [52] suggested that the minimum bond strength required for dental clinical use is 5.9–7.9 MPa and Schmage et al [40] proposed that 6–10 MPa strength is necessary to support normal orthodontic forces. Based on these studies, groups treated with MDP (AM group, 11.92 ± 1.51 MPa) and MDP containing silane primers (AMS group, 13.36 ± 2.31 MPa) after sandblasting were shown to have sufficient bond strength (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…The MDP primer was applied to increase the bond strength between the metal bracket for maxillary central incisor (Archist Bracket, Daeseung medical, Seoul, Korea) and the resin cement, after which, the bracket was bonded to the surface treated Y-TZP under a force of about 5 N [40] using the resin cement (Transbond XT, 3M Unitek, Monorvia, CA, USA). Excess resin cement was removed with an explorer, and the remaining resin cement was light cured for 20 s on each side using a halogen light curing unit (Demetron Optilux, Kerr model-VCL 401, Demetron Research, Danbury, CT, USA) at an angle of 45°.…”
Section: Methodsmentioning
confidence: 99%
“…Shear loads are among the most common and most destructive forces applied in the oral environment, which can cause debonding of brackets (15). Some researchers have attempted to improve the bond strength of orthodontic attachments to amalgam and porcelain (16) but studies on methods to improve the bond strength of orthodontic brackets to aged composite restorations are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic restorations, such as ceramic crowns or veneers, which are adhesively bonded to teeth, can be nowadays more often found in orthodontic patients because of an increasing number of adult patients who ask for a treatment [2]. Several methods have been suggested to strengthen the bond strength between ceramics and brackets: it was described to roughen the porcelain with diamond burs, green stones or abrasive disks [2,4]. Others described for getting more retention to cut a retention cavity in the ceramic surface [5].…”
Section: Introductionmentioning
confidence: 99%
“…The danger in handling hydrofluoric acid is extreme, as skin saturation with the acid in areas of only 25 square inches (160 cm 2 ) may be relatively painless, yet ultimately fatal. High concentrations of hydrofluoric acid and hydrogen fluoride gas will also quickly destroy the corneas of the eyes [2,4].…”
Section: Introductionmentioning
confidence: 99%